On shear reinforcement design of structural concrete beams on the basis of theory of plasticity - Jensen, Bjarne Christian; Lapko, Andrzej (Journal of Civil Engineering and Management, 2009)
Modern design of reinforced concrete structural members for shear is based on the theory of plasticity. This paper is written to contribute to the understanding of the inclination of the concrete strut in the inclined strut model for design of shear reinforcement in beams, which among others are used in Eurocode 2. The problem of inclination of the compression strut in truss model is analysed depending on shear reinforcement ratio and effectiveness ratio of concrete strength for compression. Also the understanding of necessary ductility in steel reinforcing bars is discussed in the paper and especially the needs of tests on translation capacity of the shear failure are here analysed. To explain these problems the paper gives a short introduction to the theory of plasticity of reinforced concrete in shear and the background for the equations, which are used in shear design according to Eurocode 2. Santrauka Šiuolaikinis gelžbetonio elementų skersinės armatūros skaičiavimas pagrįstas plastiškumo teorijos principais. Straipsnyje pateikti sijų skersinės armatūros skaičiavimo ypatumai, taikant įstrižojo statramsčio modelį, kuris taikomas ir Eurokode 2. Išnagrinėtas gniuždomojo strypo pavertimas santvaros modelyje, atsižvelgiant į skersinės armatūros ir efektyvaus gniuždomojo betono stiprio santykį. Aptartas armatūrinio plieno strypų stamantrumas, akcentuota sijų laikomosios galios šlyčiai eksperimentinių tyrimų būtinybė. Pateiktas gelžbetoninių sijų šlyties skaičiavimas, taikant plastiškumo teorijos principus. Aptartas Eurokode 2 šlyties skaičiavimams taikomų priklausomybių teorinis pagrindas. First Published Online: 15 Oct 2010 Reikšminiai žodžiai: gelžbetoninės sijos, projektavimas šlyčiai, betono plastiškumas, ilginio metodas, įstrižojo plyšio plotis.